Profile of patients hospitalized in a burn treatment center in northern Paraná - Flávia Mendonça da Silva Oussaki; Lilian Denise Mai; Mariana Sbeghen Menegatti (Revista Brasileira de Cirurgia Plástica)
Introduction: Burns are injuries arising from heat and represent a serious public health problem in the world due to physical or psychological sequelae of permanent character, and require specialized investment and quality. The objective is to know the profile of patients hospitalized in a burn treatment center in northern Paraná in 2012. Methods: Retrospective, descriptive and quantitative analysis research, conducted in 2013, with data collected from 241 clinical records of patients treated at a burn treatment center in northern Paraná in 2012. Analyses of percentage and incidence of cases were performed. Results: Readmission was present in 8% of the cases,70% of them were men, and 59% were adults; the patients had as their origin the patients originated from the regional health center in 44% of cases in 44% of the cases; the time to hospital stay was equal to or greater than three days in 38% of the cases and the mean length of stay was 17 days. Accidents in the domestic environment stood out in 75.5%; were the main causal agents of liquid alcohol: 32%, followed by scalding: 31%; the parts of the body most affected were face, upper limbs, trunk and lower limbs. There was death in 14%, reaching 44% of the elderly attended. Conclusion: Burns is a problem that affects both sexes and different age groups, triggering physical, emotional and socioeconomic consequences. These injuries are a challenge for public policies and the health system, requiring investments in specialized services and treatments, in addition to prevention strategies.